THE EFFECT OF BODY WEIGHT ON THE SIZE OF THE SCROTUM OF BALINESE CATTLE - Pedro Armengol Josua Efi; Reni Ratni Dapawole; Muh. Akramulloh (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study aimed to determine the effect of body weight on scrotal circumference in Bali bulls. Bali cattle are one of Indonesia's indigenous genetic resources with high adaptability, good productivity, and an important role in national beef production. The study employed a descriptive method through observation and evaluation of exterior performance. The research sample consisted of 10 Bali bulls grouped by age, namely 1–2 years and 3–5 years, with five animals in each group. The parameters observed were body weight and scrotal circumference. Body weight was measured using a manual scale, while scrotal circumference was measured using a measuring tape at the largest part of the scrotum. Data were analyzed using regression and correlation analyses with IBM SPSS version 25.0. The results showed that the average body weight of Bali bulls was 260.80 ± 7.80 kg, while the average scrotal circumference was 25.60 ± 3.27 cm. Regression analysis revealed a very strong positive relationship between body weight and scrotal circumference, with a correlation coefficient (r) of 0.976 and a coefficient of determination (R²) of 0.952. These results indicate that 95.2% of the variation in scrotal circumference was influenced by body weight, while the remaining 4.8% was affected by other factors such as age, genetics, nutrition, health status, and management practices. The regression equation obtained was Y = 250.054 + 5.910X. Based on the findings, it can be concluded that body weight has a highly significant effect on the scrotal circumference of Bali bulls. An increase in body weight is associated with an increase in scrotal circumference. Therefore, body weight can be used as one of the selection criteria for superior breeding bulls to support the improvement of productivity and genetic quality of Bali cattle.